L’eau dans les paysages de l’énergie - Sylvie Laroche; Nicolas Tixier (Projets de Paysage)
The findings presented in this article are the fruit of interdisciplinary research on the energy and environmental resource challenges of an urban development project on the Grenoble Peninsula. On this site, water-related energy systems are used to collect, convert and/or distribute energy and water. We propose to address the diversity of these future water resources through two concepts. One of these concepts is that of a socio-energetic node at the intersection of major networks and sources of renewable energy and the other is that of the interfaces between the aquifer and its atmospheric and terrestrial environments. Transect representations are used to reveal this semi-sociotechnical, semi-geographical landscape in order to compare the two approaches and to organise a process of collective debate and decision-making on the interrelations between natural resources, energy uses and water landscapes.